Cadmium, an Environmental Contaminant, Exacerbates Alzheimer’s Pathology in the Aged Mice’s Brain - Ali, Tahir; Khan, Amjad; Alam, Sayed Ibrar; Ahmad, Sareer; Ikram, Muhammad; Park, Jun Sung; Lee, Hyeon Jin; Kim, Myeong Ok (Frontiers in Aging Neuroscience, 2021)
Cadmium (Cd) is an environmental contaminant, which is a potential risk factor in the progression of aging-associated neurodegenerative diseases. Herein, we have assessed the effects of chronic administration of Cd on cellular oxidative stress and its associated Alzheimer’s disease (AD) pathologies in animal models. Two groups of mice were used, one group administered with saline and the other with Cd (1 mg/kg/day; intraperitoneally) for three months. After behavioral studies, the molecular/biochemical (Immunoblotting, ELISAs, ROS, LPO, and GSH assays) and morphological analyses were performed. We observed an exacerbation of memory and synaptic deficits in chronic Cd injected mice. The sub-acute and chronic Cd escalated reactive oxygen species (ROS), suppressed the master antioxidant enzymes e.g. nuclear factor-erythroid 2 related factor 2 and heme oxygenase-1, and evoked stress kinase phospho-c-Jun N-terminal kinase 1 signaling pathways, which may escalates AD pathologies possibly associated with amyloidogenic processes. These findings suggest the regulation of oxidative stress/ROS and its associated amyloid beta pathologies for targeting the Cd-exacerbated AD pathogenesis. In addition, these preclinical animal studies representing a paradigm for epidemiological studies of human population, exposed to chronic and subacute of Cd and suggesting avoiding environmental contaminants.